Synthesis of a Zeolitic Imidazolate–Zinc Metal–Organic Framework and the Combination of its Catalytic Properties with 2,2,2-Trifluoroethanol for N-Formylation - Alamgholiloo, Hassan; Rostamnia, Sadegh; Hassankhani, Asadollah; Banaei, Reza (Synlett, 2018)
A novel protocol is reported for the N-formylation of amines with formic acid by using the nanoporous zeolitic imidazolate framework ZIF-8 as a heterogeneous catalyst in 2,2,2-trifluoroethanol.
Keywords: metal–organic frameworks; trifluoroethanol; zeolites; formylation; amines